2019
DOI: 10.1029/2019jc014965
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mesoscale Features on Mixed Layer Dynamics in the Arabian Sea

Abstract: During the summer monsoon season from June through September, low‐level winds from the Findlater Jet induce strong mesoscale activity and seasonal deepening of the mixed layer. For the first time, we have investigated the impact of mesoscale features on the strong intraseasonal variability of the mixed layer depth in the Arabian Sea using simulations from a reanalysis version of the HYbrid Coordinate Ocean Model and the European Centre for Mid‐range Weather Forecasting ERA‐Interim product. We identify and trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The horizontal resolution is 0.08° (∼9 km) at the equator and approximately 6.5 km at midlatitude, making it globally eddy‐resolving for the mesoscale features that are addressed in this study. The hybrid coordinate system (that is isopycnal in the open stratified ocean, but smoothly transitions to z coordinates in the ocean mixed layer and sigma coordinates in coastal regions) has 41 layers vertically with potential density referenced to 2,000 m. The HYCOM reanalysis has been extensively validated and used in previous studies (e.g., Chen et al., 2017; Jensen et al., 2018; Luecke et al., 2017; Rydbeck et al., 2019; Trott et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal resolution is 0.08° (∼9 km) at the equator and approximately 6.5 km at midlatitude, making it globally eddy‐resolving for the mesoscale features that are addressed in this study. The hybrid coordinate system (that is isopycnal in the open stratified ocean, but smoothly transitions to z coordinates in the ocean mixed layer and sigma coordinates in coastal regions) has 41 layers vertically with potential density referenced to 2,000 m. The HYCOM reanalysis has been extensively validated and used in previous studies (e.g., Chen et al., 2017; Jensen et al., 2018; Luecke et al., 2017; Rydbeck et al., 2019; Trott et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The reanalysis uses the Navy Coupled Ocean Data Assimilation (NCODA) system for data assimilation, utilizing the model forecast as a first guess in a 3-D variational scheme and assimilating available satellite altimeter observations, in-situ Sea Surface Temperature (SST), in-situ vertical temperature and salinity profiles from XBTs, Argo floats and moored buoys (Cummings, 2005;Cummings & Smedstad, 2013 equator and approximately 6.5 km at midlatitude, making it globally eddy-resolving for the mesoscale features that are addressed in this study. The hybrid coordinate system (that is isopycnal in the open stratified ocean, but smoothly transitions to z coordinates in the ocean mixed layer and sigma coordinates in coastal regions) has 41 layers vertically with potential density referenced to 2,000 m. The HYCOM reanalysis has been extensively validated and used in previous studies (e.g., Chen et al, 2017;Jensen et al, 2018;Luecke et al, 2017;Rydbeck et al, 2019;Trott et al, 2019).…”
Section: Datamentioning
confidence: 99%
“…An important and interesting forcing that influences trends in SSS (and salinity throughout the mixed layer) is that of the vertical transport of salinity between the surface ocean and interior ocean, primarily driven by eddies. This applies to both mesoscale and submesoscale eddies, though mesoscale eddies tend to induce stronger vertical motions that act as a restoring force to restratify the mixed layer (Trott et al, ). However, the largest submesoscale vertical velocities associated with this phenomenon can penetrate 200 m below the mixed layer (Yu et al, ).…”
Section: Salinity Variability In the Tropical Indian Oceanmentioning
confidence: 99%
“…The heat flux biases are due to the poor representation of cloud cover and specific humility in the TIO (Li & Xie, 2012;Parekh et al, 2011), while the overestimated mixing is a result of the excessive surface salinity due to the lack of freshwater inflow from the West India Coastal Current and the Indonesian through flow (Parekh et al, 2016), as well as the overestimated evaporation (Chowdary et al, 2016). An inaccurate representation of mesoscale eddies can lead to biases in vertical mixing and is also proposed to contribute to the cold SST bias in the TIO (He et al, 2020;Trott et al, 2019). Rahaman et al (2020) showed that the coupled feedbacks in the TIO can magnify the TIO SST bias in model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%